(untitled) (CIENCIA Y TECNOLOGÍA AGROPECUARIA, 2024)
Grain legumes, such as beans Phaseolus vulgaris L., are essential in human nutrition due to their high protein content, complex carbohydrates and low-fat content, being an economical and nutritionally adequate option compared to products of animal origin. In Venezuela, beans are a strategic crop due to their protein content and their ability to adapt to various soils and adverse climates, in addition to improving soil fertility through nitrogen fixation. A study was carried out in the Mundo Nuevo sector, Ezequiel Zamora municipality, Cojedes, whose objective was to identify various pests that affect the bean crop. The results indicate the presence of borer bugs Andrector arcuatus (Olivier) and Andrector ruficornis (Olivier), leafhoppers Empoasca kraemeri (Ross y Moore) and Agrosoma spp.) and thrips (Thrips sp.). These insects cause significant damage, such as leaf perforations, sap sucking, and transmission of viral diseases, negatively affecting crop yields. In addition, beneficial insects were identified such as Podisus sp. (Hemiptera: Pentatomidae), Cycloneda sanguinea (L.) (Coleoptera: Coccinellidae), Diptera: Tachinidae, and Zelus sp. (Hemiptera: Reduviidae). These bioregulators play an important role in the agricultural ecosystem by controlling pest insect populations. Therefore, it is crucial to implement agronomic practices that favor the conservation of these beneficial insects, such as the use of colored traps and natural repellents, instead of chemicals. Beans are not only an essential nutritional source but also a vital crop for food security in Venezuela. However, the presence of various pests represents a considerable challenge for farmers. The identification and proper management of these pests, along with the conservation of beneficial insects, are essential to ensure the sustainability and success of bean cultivation in the Mundo Nuevo sector and other similar regions.